Edukasi: Optimasi Menggunakan Metode Simpleks Pada Usaha Bahan Bakar Minyak Berskala Kecil - Tirsa Ninia Lina; Matheus Supriyanto Rumetna (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The COVID-19 pandemic has forced small-scale businesses to innovate. One of them is a business owned by Mr. Ruddy which sells gasoline and pertalite types of fuel oil. Before the pandemic hit, this business could be said to be running smoothly, but during the pandemic this business began to be deserted from consumers. During the pandemic, the Sorong city government implemented regulations related to PPKM. This regulation also contributes to the reduction of consumers for Mr. Ruddy's business, because people are limited in their mobility. Seeing the situation experienced by Mr. Ruddy's business, the PkM team of the Information Systems Study Program at Victory Sorong University offers an educational program on the use of Linear Programs by utilizing the Simplex method and information technology in the form of POM-QM software for windows version 5.3. The purpose of this educational program is to share knowledge to help small-scale businesses, especially Mr. Ruddy's businesses, to continue to innovate and survive during the pandemic. Where Mr. Ruddy can gain knowledge that can be used for decision making in business operations.